A Class of Rumor Spreading Models with Population Dynamics *Supported by National Natural Science Foundation of China under Grant Nos. 11275017 and 11173028. (December 2018) - Dong 董, Suyalatu 苏雅拉图; Huang 黄, Yong-Chang 永畅
Abstract: Based on the characteristics of rumor spreading in online social networks, this paper proposes a new rumor spreading model. This is an improved SIS rumor spreading model in online social networks that combines the transmission dynamics and population dynamics with consideration of the impact of both of the changing number of online social network users and different levels of user activity. We numerically simulate the rumor spreading process. The results of numerical simulation show that the improved SIS model can successfully characterize the rumor spreading behavior in online social networks. We also give the effective strategies of curbing the rumor spreading in online social networks .